ANALISIS SOSIOLOGI SASTRA NOVEL KEMBANG JEPUN KARYA REMY SYLADO - Silado, Remmy (Humanis; Volume 12. No.2. Agustus 2015, 2015)
This research relies on the sociological analysis point of view that literacy is a social and cultural document. The main focuses of analysis are: first is the structure of the novel especially related to the intrinsic structure and the relation between structure to build a coherent story. Secondly, this research focuses on the sociological aspect of the novel which can be categorized into social, moral, cultural and economical aspects. This research adopts structural and sociological theories of literacy. Structural theory is used to analyze the intrinsic structure of the novel and the relation between those structures while sociological theory is used to explain the sociological aspect of the novel. This research relies on Umar Junus’s (1986) sociological theory of literacy which argues that literacy is part of a social and cultural document. The research reveals that the theme of this novel is about the struggle and love sacrifices of Keke, a geisha in Surabaya between 1920 until 1983, plotted in a forward progressive plot. There are four sociological aspects of the novel. Firstly is the social aspect which explore the sociological setting of geisha life in Shinju, Surabaya. Secondly is the moral aspect, dominated by Keke as the main character as geisha which seen by society similar to prostitute and received negative stereotypes. Thirdly is the cultural aspect focuses on Keke’s cultural transformation and acculturation processes to become a geisha. Lastly, economical aspect that separate society into three economical classes: the upper class, the middle class, and lower class.
Keywords: geisha, Surabaya, “Kembang Jepun”